Antimicrobial resistance of Escherichia coli and Salmonella in raw retail table eggs in Lusaka, Zambia - Kapena, Munsanda Susan (Vet World, 2020)
BACKGROUND AND AIM: Antimicrobial resistance (AMR) has risen as a serious cross-cutting global public health emergency. At the center of this emergency, foods of animal origin have particularly been singled out as possible drivers despite the paucity of information. This study has been formulated to provide answers to the identified critical gaps in the food safety industry and the public health sphere. In particular, this study was undertaken to investigate the AMR of Escherichia coli and Salmonella in raw retail table eggs in Lusaka, Zambia. MATERIALS AND METHODS: Accordingly, a cross-sectional study to determine antibiotic susceptibility of E. coli and Salmonella from raw retail table eggs was undertaken. Standard bacteriological methods involving culture and phenotypic characterization were applied. A total of 1080 raw table eggs pooled into composite samples (five eggs per composite sample) translating into 216 distinct and independently identifiable compounded sample units were collected from randomly selected supermarkets and open markets over 4 months (August 2018-November 2018). The eggs were screened for the presence of E. coli and Salmonella within 24 h of sample collection by standard microbiological methods. The Kirby–Bauer disk diffusion technique was used for antimicrobial susceptibility testing using a panel of nine different antibiotics. RESULTS: A total of 216 pooled egg samples were analyzed at two levels of contamination, (i) eggshell and (ii) egg content. From the eggshell, five compounded samples were positive for Salmonella spp. representing 2.31% (5/216), while 34.26% (74/216) were positive for E. coli. On the other hand, samples from egg contents were negative for Salmonella and E. coli. Eggshells were more likely to be contaminated by E. coli compared to the egg content (χ(2)=20.95, p<0.0001). Imipenem was 100% effective against E. coli isolates. With Salmonella, high resistance was seen in 80% against tetracycline (TE) and 60% to ampicillin (AMP). E. coli showed 94.6% resistance to colistin sulfate, 83.8% resistance to TE, and 59.5% resistance to AMP. CONCLUSION: Overall, this study has been able to demonstrate the presence of E. coli and Salmonella outside and inside table eggs in Zambia. It has also shown the resistance of identified isolates which poses a serious public health concern given the consumption patterns of these table eggs.